Invasive Effect of Exotic Pines : a Case Study in Kalika Forest - Bhattacharyya, G.; Joshi, G. C.; Tewari, L. M. (Indian Forester, 2010)
Present study was conducted to determine the invasive impacts of the most prolific exotic pines on the natural ecosystem in Kalika forest of West Almora Forest Division, Uttarakhand. Among the angiospermic ground flora, 32 species have been identified belonging to 19 families. Asteraceae shows the maximum predominance with 9 species followed by Rosaceae represented by 3 species.Lamiaceae, Onagraceae and Pappilionaceae are represented by 2 species each. All other families have shown only one representative member. The study shows that Pinus patula appears to be invasive for the local flora followed by P. greggii, P. densiflora and P. wallichiana. While P. regitaeda tends to counteract the aggression of P. patulaand P. greggii.